Human Resource Management Practices and Work Productivity in Construction Firms - Budiman, Dendy Arif; Dwiatmadja, Christantius; Sugiarti, Rini (Academia Open, 2026)
General Background: Human Resource Management (HRM) is a critical determinant of organizational success, particularly in labor-intensive industries where employee productivity directly shapes performance outcomes. Specific Background: Within construction service organizations, HRM practices such as planning, recruitment, evaluation, and motivation are systematically implemented to sustain operational efficiency and workforce performance. Knowledge Gap: Despite the recognized importance of HRM, practical challenges such as managerial inefficiencies and nepotism within family-based organizational structures may hinder optimal productivity outcomes. Aims: This study aims to examine the role of HRM in supporting work productivity while identifying facilitating and inhibiting factors within the organizational setting. Results: The findings indicate that structured HRM functions—including strategic recruitment, multi-level performance evaluation (daily, monthly, quarterly), incentive and punishment systems, flexible work arrangements, and supportive work environments—contribute to sustained productivity. However, nepotism emerges as a key structural constraint affecting objectivity and employee morale. Novelty: This study provides an integrated qualitative perspective linking managerial functions, workplace conditions, and organizational culture to productivity within a construction industry context. Implications: Strengthening merit-based policies and professional HRM practices is essential to ensure sustainable productivity, organizational resilience, and long-term competitiveness in construction service firms. Highlights: Structured managerial processes enable consistent workforce monitoring and task execution. Compensation mechanisms and working conditions shape discipline and output stability. Informal power structures reduce fairness and weaken workforce morale. Keywords: Role, Human Resource Management, Work Productivity.